Depression symptoms prevalance and affecting factors in middle and elder aged women who live in Elazi? Yenimahalle Training and Research Health Department - Açik, Yasemin; Güngör, Leyla; Kulo?lu, Murat; Atmaca, Murat; Güngör, M. Yüksel; O?uzöncül, A. Ferdane (My University, 2003)
Depression is a significant public health problem in respect to its prevalence as well as its consequences. As to the clinical and epidemiological studies, depression is more frequently encountered in females. In this study, it has been aimed to determine the depression symptoms prevalence and affecting factors in middle and elder aged women who live in Elazi? Yenimahalle Training and Research Health Department region. Among 6213 middle and elder aged women who lived in the Health Department region, 361 were selected with Randomized Numbers Scale and 346 of them (95.8) were attained in recurring visits. Each women participated in the study were applied Hamilton Depression Grading Scale and those who got 14 or more points were accepted as showing depression symptoms. At the end of the research 113 women (32.6%) were accepted to show depression symptoms. According to our study, depression symptoms were more frequently encountered in the women who were divorced or whose husbands died (p=0.006), and 25.7% of the 35-39 year-old women; 57.1% of the 70+ year-old women showed depression symptoms. Depression symptoms existed 43.0% of women who suffered from a chronic disease, 41.4% of them who had a dead child story; and 36.4% of them who weren't a school graduate. Consequently, in the middle and elder aged women who live in YMTRHD region, depression symptoms are frequently encountered, and are affected with such factors as education, marital status, monthly income, chronic illness and the existance of dead child story. For this reason, it has been found important that the health personnel who work in the first-degree health services should be given education about the diagnose and treatment of depression.
Orta ve i?leri yaşlardaki kadinlarda depresyon belirtileri sikli?i ve etkileyen faktörler
Keywords: Affecting factors; Depression; Women